Climate change and rice production in Sri Lanka: short-run vs. long-run symmetric and asymmetric effects - Samarasinghe, B. K. D. J. R.; Zhu, Yuchun; Abeynayake, N. R.; Zeng, Xuemei; Mathavan, B.; Wanninayake, R. W. W. M. P. K.; Rasheed, Somaiya; Bah, A. Salami (Frontiers in Sustainable Food Systems, 2025)
This study explores climate change's symmetric and asymmetric impacts on rice production in Sri Lanka, a crucial sector for food security in the country. The analysis utilized Autoregressive Distributed Lag (ARDL) and Non-linear Autoregressive Distributed Lag (NARDL) models. This study analyses annual data from 1952 to 2022 to capture relationships among the study variables. The ARDL findings reveal that temperature and cultivated land area have a significant long-term effect on rice production. The NARDL model reveals that positive and negative changes in climate variables have asymmetrical long-term impacts. Positive changes in temperature and rainfall lead to a notable decline in rice yields in the long term. Negative rainfall changes create a significant beneficial effect on rice production in the long term. Cultivated land area shows a significant positive impact on rice yield in the long term. The results of symmetric and asymmetric climate change impact are essential for formulating agricultural climate adaptation policies, such as promoting climate resilience rice varieties, improving irrigation and water management, developing early warning systems that promote sustainability and enhance climate adaptation strategies, ensuring food security in Sri Lanka.